(untitled) (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2025)
This article analyzes the didactic essence of the artistic views of Hafiz Khorezmii, identifies their pedagogical foundations, and discusses scientific research conducted in this area. Also, the concepts of self-awareness, communication with the inner world, and perception of beauty put forward by the creator through the word are revealed.